Strategi Efektif Pengendalian Persediaan Barang Jadi Dalam Bisnis Mochi AO Daifuku: Meningkatkan Efisiensi dan Kelayakan Operasional - Yunita, Anggita Vira; Putri, Arfie Laillya Azrawanda; Sulistyowati, Yana (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
The development of the food business is currently experiencing quite rapid growth. The reason is that more and more new foods are emerging and innovating. One of them is the sweet mochi food business "Ao Daifuku" or blue mochi which has a theme from the land of Japanese cherry blossoms. This research was conducted to explore the application of finished goods inventory planning and control in the "Ao Daifuku" mochi business which includes preparing stock of goods ready for sale, handling and sales progress, reporting data on remaining stock of finished raw materials with existing physical goods. The purpose of this writing is to determine the application of planning, controlling finished goods inventory and improving operational efficiency and business feasibility. Through in-depth field observations and practice, the author analyzes the concrete steps taken by the Ao Daifuku mochi business in finished product stock management, production processes and distribution. These findings provide deep insight into how an integrated inventory control strategy can bring significant improvements in operational efficiency, optimize product availability, and strengthen Ao Daifuku's position in the culinary industry.